ADAPTASI BUDAYA DALAM PERKAWINAN LINTAS ETNIS DI GAMPONG UJUNG PADANG KABUPATEN NAGAN RAYA - Amelia, Putri; Sopar (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
Interethnic marriage has become an increasingly common social phenomenon within Indonesia's multicultural society. Differences in cultural backgrounds in such marriages encourage a process of acculturation between spouses of different ethnicities. This study aims to explore the cultural acculturation process in interethnic marriages between Acehnese and Javanese couples in Nagan Raya Regency. A descriptive qualitative method was used, with data collected through in-depth interviews and observation. The subjects of this research were two married couples who have been together for more than two years. The findings reveal that cultural acculturation occurs through various forms of adjustment, such as in daily language, food preferences, parenting styles, and the implementation of family traditions. Cultural differences can be overcome through good communication, mutual respect, and openness between partners. The couples were able to integrate cultural elements from both sides, resulting in a harmonious household. This study suggests that both the community and the government should provide educational opportunities and cross-cultural interaction spaces to support the development of tolerance and strengthen social integration within interethnic marriages.